NON-NULL NORMAL CURVES IN THE SEMI-EUCLIDEAN SPACE E2^4 - Almaz, Fatma; Kulahci, Mihriban Alyamac (My University, 2021)
In this study, the representation formulas of non-null curves are primarily expressed in four dimensional semi-Euclidean space E24 and the non-null normal curves in E24 are examined and some certain results of describing the nun-null normal curve are presented in detail in E_2^4. In addition, some mathematical conditions are expressed for a curve given in four dimensional semi-Euclidean space E24 to be a nun-null normal curve as theorems.
Keywords: Frenet frame; normal curve; Semi-Euclidean space E2 4